The heat flow losing via earth’s surface around of Khulj hot spring - Tserendug, Shoovdor; Genden, Bayanjargal; Nasan-Ochir, Tumen; Zolbadral, Tsoodol (Mongolian Geoscientist, 2023)
In this paper, we extracted values of geomagnetic anomaly sourced in the lithosphere from the total intensity of geomagnetic that is measured on the 750 points on an area (100x100 km2) around the Khulj hot springs. The two-dimensional map of the distribution of the anomaly geomagnetic corresponding to this area was made via these extracted values of anomaly geomagnetic. The method of spectral analysis was used to estimate the Curie Point Depth, which is lost magnetic characteristics of the lithosphere with a temperature of 580o C and the depth of layer sourcing anomaly geomagnetic with high content of iron, nickel, and tungsten by these values of geomagnetic anomaly. On the Fig. 5, the isothermal Curie surface with the temperature of 580o C was visualized in three dimensions by these values of Curie Point Depth. The heat flows lost on Earth’s surface was also detected by the method of the gradient of temperature from the Curie Point Depth. And the two-dimensional map of heat flow around the Khulj hot spring was illustrated by the values of heat flows. Moreover, the average value of the heat flow for whole the area (100x100 km2) was about 60[mW/м2], and it was estimated at about 70[mW/м2], at the Khulj hot springs. When we carried out a same study near Ulaanbaatar in 2018, the average heat flows lost on Earth’s surface was determined about 40-50[mW/м2].